2020
DOI: 10.1101/2020.11.13.20231266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating the cumulative incidence of SARS-CoV-2 infection and the infection fatality ratio in light of waning antibodies

Abstract: BackgroundSerology tests can identify previous infections and facilitate estimation of the number of total infections. However, immunoglobulins targeting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been reported to wane below the detectable level of serological assays. We estimate the cumulative incidence of SARS-CoV-2 infection from serology studies, accounting for expected levels of antibody acquisition (seroconversion) and waning (seroreversion), and apply this framework using data fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 27 publications
(43 reference statements)
2
73
0
Order By: Relevance
“…Overall, our results indicate that asymptomatic and mostly unsuspected SARS-CoV-2 infections are more prevalent than currently thought. Moreover, the number of asymptomatic cases in the community could be even higher, since the seroprevalence in cross-sectional studies can be underestimated without adjustment for waning antibodies, as previously reported in studies from New York City and Connecticut [ 28 ].…”
Section: Discussionmentioning
confidence: 98%
“…Overall, our results indicate that asymptomatic and mostly unsuspected SARS-CoV-2 infections are more prevalent than currently thought. Moreover, the number of asymptomatic cases in the community could be even higher, since the seroprevalence in cross-sectional studies can be underestimated without adjustment for waning antibodies, as previously reported in studies from New York City and Connecticut [ 28 ].…”
Section: Discussionmentioning
confidence: 98%
“…At odds with our findings, waning humoral immunity in patients with SARS-CoV-2 infection has also been reported. Therefore, this raises the possibility that naturally developed humoral immunity counter to SARS-CoV-2 might not be long-lasting ( Choe et al, 2021 , Shioda et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, antibody waning may also make this interpretation challenging, as up to 5 months may have passed between the first and second specimen collection for some participants. Recently, other teams have developed algorithms to correct seroprevalence estimates for waning 20 , and we may be able to use these approaches to correct our estimates of cumulative incidence in our cohort going forward. Limitations of serological assays notwithstanding 21 , recent cross-sectional serosurveys done prior to the relaxing of physical distancing have reported cumulative incidence estimates ranging from 1.7% in Indiana to 21% in New York City, and <10% nationally as of the end of September 2020.…”
Section: Discussionmentioning
confidence: 99%